AN INVESTIGATION INTO THE CHALLENGES IN LEARNING B1 CAMBRIDGE SPEAKING SKILLS AMONG NON-ENGLISH MAJORED JUNIORS AT DONG A UNIVERSITY AND SUGGESTED SOLUTIONS - Bùi Thị Hòa Oanh, Bùi Thị Hòa Oanh; Võ Thu Uyên, Võ Thu Uyên (Tạp chí Khoa học Đại học Đông Á, 2025)
This study aims to investigate the difficulties in learning B1 Cambridge speaking among non-English majored juniors at Dong A University and to propose solutions to improve their practice effectiveness. Employing a quantitative research method, the study gathers data through both online and in-person student surveys, along with a separate questionnaire for teachers to suggest improvement strategies. The data, analyzed using statistical tools in Google Forms, highlights key obstacles and suggests remedial measures. The research findings indicate that the majority of students struggle with B1 Speaking skills due to limited vocabulary, weak grammar, poor listening skills, incorrect pronunciation, lack of confidence, and insufficient practice opportunities. Based on these findings, the study proposes several practical solutions, including practicing with sample test questions, applying the shadowing method, and utilizing learning tools such as VirtualSpeech to create an immersive speaking environment. It is hoped that the study will offer practical recommendations to support students in enhancing their Speaking skills for the Cambridge B1 exam, while also contributing to the foundation for future research on effective language teaching methods.